Awareness on Prevention of Complication Related to Immobility among Caregivers of Bedridden Patients in Tertiary Health Care Center in Chitwan - Dhakal, Binita (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Immobility is a condition in which a person is unable to move freely or movement is restricted for medical reasons. Prolonged bed rest and immobilization inevitably leads to complications. Caregivers play a vital role in preventing the complications of immobilization and avoiding discomfort for the patient. This study aims to assess awareness on prevention of complications of immobility among caregivers of bedridden patients admitted in tertiary health care center. Methods: A descriptive cross-sectional research design was used to assess 66 caregivers of college of medical sciences by using non-probability convenience sampling technique. Data was collected by using self-administered questionnaire to assess awareness through face-to-face interview method. Obtained data were analyzed by using descriptive and inferential statistics using IBM SPSS 16. Results: Study findings revealed that the mean age of the respondents was 18 years with mean age 18 ± 11.87 and majority (54.5%) were female with higher percentage of respondents’ involvement in agriculture (28.3%). Majority (68.2%) of the respondents stayed in hospitals for 1 to 5 days and 51.5% respondents had no previous experience of hospital stays. Among the total respondents, majority (83.3%) had inadequate awareness on prevention of complication related to immobility which varied with respondent’s gender (p=0.047), educational level (p=0.001), occupation (p=0.0026) and information from television (p=0.005). Conclusions: Majority of the respondents had inadequate awareness on prevention of complication related to immobility. Findings emphasize that awareness programs should be implemented time to time in hospital settings to update the caregivers in relation to preventive measures of complications of immobilization.